Gel-Based Triboelectric Nanogenerators for Flexible Sensing: Principles, Properties, and Applications - Lu, Peng; Liao, Xiaofang; Guo, Xiaoyao; Cai, Chenchen; Liu, Yanhua; Chi, Mingchao; Du, Guoli; Wei, Zhiting; Meng, Xiangjiang; Nie, Shuangxi (Nano-Micro Letters, 2024)
The rapid development of the Internet of Things and artificial intelligence technologies has increased the need for wearable, portable, and self-powered flexible sensing devices. Triboelectric nanogenerators (TENGs) based on gel materials (with excellent conductivity, mechanical tunability, environmental adaptability, and biocompatibility) are considered an advanced approach for developing a new generation of flexible sensors. This review comprehensively summarizes the recent advances in gel-based TENGs for flexible sensors, covering their principles, properties, and applications. Based on the development requirements for flexible sensors, the working mechanism of gel-based TENGs and the characteristic advantages of gels are introduced. Design strategies for the performance optimization of hydrogel-, organogel-, and aerogel-based TENGs are systematically summarized. In addition, the applications of gel-based TENGs in human motion sensing, tactile sensing, health monitoring, environmental monitoring, human–machine interaction, and other related fields are summarized. Finally, the challenges of gel-based TENGs for flexible sensing are discussed, and feasible strategies are proposed to guide future research. Highlights: 1 Typical structures/working mechanisms of gel-based triboelectric nanogenerators and performance advantages of gel materials reviewed. 2 Optimization of hydrogels, organogels, and aerogels for triboelectric nanogenerators in flexible sensing summarized. 3 Applications, challenges, and future development directions of gel-based triboelectric nanogenerators in flexible sensing are discussed.